2019
DOI: 10.4103/jfmpc.jfmpc_653_19
|View full text |Cite
|
Sign up to set email alerts
|

Integrated primary palliative care model; facilitators and challenges of primary care/family physicians providing community-based palliative care

Abstract: Introduction:Patients with advanced cancer often suffer from complex symptoms necessitating constant supervision and management. Primary care/family physicians act as an important bridge between the patients in the community and the specialists in the hospital ensuring continuity of care.Materials and Methods:The present paper explored the facilitators and challenges in providing home-based palliative care as perceived by the primary care/family physicians (PCP/FP).Results:62 physicians reported that they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…In 16.25% of the cases, we could liaise with the family physicians and handle the patient's issues. These findings were similar to the integrated model postulated by Atreya et al 25 in their study. Despite the pandemic situation, these family physicians worked relentlessly to assist in caring for these patients.…”
Section: Discussionsupporting
confidence: 93%
“…In 16.25% of the cases, we could liaise with the family physicians and handle the patient's issues. These findings were similar to the integrated model postulated by Atreya et al 25 in their study. Despite the pandemic situation, these family physicians worked relentlessly to assist in caring for these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Community based PC (CBPC) aims to integrate PC into local healthcare systems and has been shown to improve patient and caregiver satisfaction, quality of life (QoL), reduce health care expenditure and hospital admissions at end-of-life (EOL) [8,9]. However, there is scarcity of CBPC services in India [10][11][12]. One unique and sustainable CBPC model is neighbourhood network in PC (NNPC); operational in the southern Indian state of Kerala [13].…”
Section: Introductionmentioning
confidence: 99%
“…One unique and sustainable CBPC model is neighbourhood network in PC (NNPC); operational in the southern Indian state of Kerala [13]. However, NNPC is exclusive to the region because of unique sociopolitical-economic environment, availability of resources and their mobilization strategies, awareness, and varying degrees of economic self-su ciency, which were integrated through innovative approaches [11,13]. Above factors responsible for NNPC's sustainability limits its applicability to other regions with different socio-political context [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Studies have shown that applying the integrated medical care rounds model to concurrent radiotherapy and chemotherapy for cervical cancer is conducive to promoting the recovery of patients, alleviating anxiety and depression of patients, reducing the occurrence of complications, and improving the quality of life of patients. [21] A qualitative study of medical staff's cognition and attitude towards patient reporting outcomes shows that the interviewed medical staff generally hold a positive and open attitude towards the concept of patient reporting outcomes, and nursing staff should formulate scientific and feasible application plans to promote patients. [22] After nursing in this study, the anxiety, depression, fatigue, and anger of the 2 groups of patients after cervical cancer surgery were significantly improved, and the emotional response score of the observation group was significantly lower than that of the control group.…”
Section: Discussionmentioning
confidence: 99%